Studenci z niepełnosprawnością w bibliotece akademickiej: przegląd tematyki i zagadnień = Students with disabilities in the academic library: a review of problems and issues - Adaszyńska, Ewa; Kuncewicz, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Students with disabilities have full rights to function effectively and actively in the educational and social space of the university. The task of the academic community is to create favourable conditions for studying, learning and participating in academic life, as well as taking measures to counteract social and environmental inequality.The major characteristic of the above measures is the creation of a library whichis open to the needs of students with disabilities ? a library without design-related organizational or mental barriers. The problems connected with issues pertaining to academic libraries concern the following areas: legal regulations, adaptation of buildings and library space, access to digital information space and new technologies, and education and awareness raising among the library staff pertaining to the provision of services and support to students with different levels of disability in using the resources and services.The study presents the documents and guidelines designed by the International Federation of Library Associations and Institutions. It discusses the case of theUniversity of Zielona Góra Library and refers to the examples of other university libraries in Poland.
Keywords: studenci z niepełnosprawnością; biblioteka akademicka; Biblioteka Uniwersytetu Zielonogórskiego; szkolnictwo wyższe; students with disabilities; academic library; Library of the University of Zielona Góra; higher education